Waste remanufacturing modeling originated from household equipment - de Oliveira Simonetto, Eugênio; D. Putnik, Goran; Butala, Peter; Caetano Monteiro, António Alberto (Brazilian Journal of Operations & Production Management, 2018)
The growing generation of solid waste is one of the environmental problems that have most affected the world population in recent years. The solid waste generated from home appliances and information technology devices are one of the classes that concern the international community, since they have high toxicity and high potential of environmental pollution. This article presents the design, implementation and testing of a model aimed to evaluate the possibility of their remanufacturingfrom the waste originated from household equipment. In the case developed for the article the waste of printers (inkjet and laser), scanners and computerswere evaluated forthe development of a three dimensional printer (3D Printer). The System Dynamics methodology was used to implement the model, and to verify and validate it.There experiments using three scenarios were developed: an uncertainty scenario with a random rate between 25% and 75% of waste reuse; thegrowth scenario with a rate from 25% to 75% of waste reuse (growth of 5% per year) and; static scenario with a rate of 50% of waste reuse during the simulated time.Results generated by the simulation modelshow that the remanufacturing is a viable alternative for the reutilization of the discarded household equipment.